Motivation and Social Skills in Nursing Students Compared to Physical Education Students - Sánchez-Bolívar, Lionel; Escalante-González, Sergio; Martínez-Martínez, Asuncion (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
One of the relevant factors that explain human behavior, in the acts that develops in daily life, is motivation. The aim of this study was to determinate the level of motivation and social skills in nursing degree student and compare with the level of motivation of physical education students. A descriptive and correlational study, with a cross-sectional design was used in this research (n= 101; 22.03 + 5.8 years old), using the Spanish version of the Situational Motivation Scale (SIMS). It can be highlighted that there is a predominantly female student population in this campus, with a higher motivational level. The predominant religion is the Christian/Catholic, counting with mean values in identified regulation superior to those of the rest. Regarding social skills, thinking (optimistic or pessimistic), empathy and assertiveness are the skills that influence the degree of motivation of students. Regarding the level of motivation, Nursing students show a medium-high level and Physical Education, a high level. Motivation is intrinsic in nursing students and more extrinsic in Physical Education students, although there are also high levels of intrinsic motivation.